Pengaruh Financial Technology Terhadap Kinerja Usaha Mikro Kecil dan Menengah (UMKM) - Senda Yunita Leatemia; Theresia Febiengry Sitanala; Adonia Anita Batkunde; Paskanova Christi Gainau (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Micro, Small and Medium Enterprises (MSMEs) are a sector that contributes significantly to Indonesia's economic growth. Therefore, it is very important to pay attention to the growth and development of these businesses. Business growth and development can be simplified by the concept of business performance. In the current digital era, the performance of a business is not only determined by conventional (traditional) methods. Business actors are required to involve themselves in the development of technology and information so that their business remains alive (going concern). On the other hand, many business actors are comfortable with conventional practices, so they are reluctant to move to modern practices. This study aims to examine the effect of financial technology represented by cashless payment and market aggregator on the performance of MSMEs. This research employs quantitative method. Population was all SMEs in Ambon City and the sampling technique was purposive sampling. This technique succeeded in getting 100 QRIS MSME users spread across the Ambon City area. The data was collected through questionnaires which were distributed directly to business actors at their business location. The data analysis technique uses multiple linear regression analysis with the result that cashless payments have no significant effect on business performance, while market aggregators have a significant effect on the performance of MSMEs in Ambon City.